2006
DOI: 10.1103/physrevlett.97.157001
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Dynamics and the Fulde-Ferrell-Larkin-Ovchinnikov State in a Magnetic-Field-Induced Organic Superconductor

Abstract: Under special conditions, a superconducting state where the order parameter oscillates in real space, the so-called FFLO state, is theoretically predicted to exist near the upper critical field, as first proposed by Fulde and Ferrell, and Larkin and Ovchinnikov. We report systematic measurements of the interlayer resistance in high magnetic fields to 45 T in the two-dimensional magnetic-field-induced organic superconductor lambda-(BETS)2FeCl4, where BETS is bis(ethylenedithio)tetraselenafulvalene. The resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
110
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 26 publications
1
110
0
Order By: Relevance
“…33,34) While a Larkin-Ovchinnikov (LO) state, characterized by the magnitude modulation of the superconducting order parameter, is expected in centrosymmetric superconductors, 35) a Fulde-Ferrell (FF) state, a "helical phase" with an essentially constant order parameter magnitude, 3,[9][10][11][12][13][14][15] could appear in non-centrosymmetric superconductors exposed to a magnetic field. Although experimental indications of the realization of an LO phase have been found for the heavy-fermion superconductor CeCoIn 5 , 36,37) organic superconductors, [38][39][40] ultracold fermion gases with a population imbalance, 41) and nuclear matter, 42) there has been no experimental evidence of the helical phase in non-centrosymmetric superconductors so far. In this paper, we show that a complex-stripe phase, which can be viewed as intermediate between FF and LO states, may exist in locally non-centrosymmetric multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…33,34) While a Larkin-Ovchinnikov (LO) state, characterized by the magnitude modulation of the superconducting order parameter, is expected in centrosymmetric superconductors, 35) a Fulde-Ferrell (FF) state, a "helical phase" with an essentially constant order parameter magnitude, 3,[9][10][11][12][13][14][15] could appear in non-centrosymmetric superconductors exposed to a magnetic field. Although experimental indications of the realization of an LO phase have been found for the heavy-fermion superconductor CeCoIn 5 , 36,37) organic superconductors, [38][39][40] ultracold fermion gases with a population imbalance, 41) and nuclear matter, 42) there has been no experimental evidence of the helical phase in non-centrosymmetric superconductors so far. In this paper, we show that a complex-stripe phase, which can be viewed as intermediate between FF and LO states, may exist in locally non-centrosymmetric multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…These well-studied materials [8][9][10][11][12] are strong type-II spin-singlet superconductors of high purity with long mean free pathes. During the last years, there indeed have been a number of reports giving growing evidence for the existence of an FFLO state in 2D organic superconductors [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays such states are collectively known as the Fulde-FerrellLarkin-Ovchinnikov (FFLO) state. Recently the FFLO state has received renewed interest due to experimental evidence of its existence in various superconductors, 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27 and the (thus far theoretical) possibility of its realization in trapped cold atom systems, 28,29 nuclear matter and in the core of neutron stars. 30 Soon after the original work of FFLO, it was found that the FFLO state is very sensitive to the presence of impurities, and eventually suppressed when the disorder strength reaches certain critical value.…”
Section: Introductionmentioning
confidence: 99%